2018
DOI: 10.1016/j.chemosphere.2017.10.113
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the lethal and behavioral effects of commercial insecticides on the parasitoid wasp Copidosoma truncatellum

Abstract: Copidosoma truncatellum (Hymenoptera: Encyrtidae) is an important parasitoid wasp of the soybean looper, Chrysodeixis includens, but its effectiveness can be severely curtailed by the application of certain insecticides. Therefore, to identify insecticides that are potentially compatible with C. truncatellum, the lethal and behavioral effects of nine chemicals used to control the soybean looper were evaluated for their toxicity to the wasp. Chlorantraniliprole, chlorfenapyr, flubendiamide, and indoxacarb were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…IMD was thought to impede information receiving and processing in N. vitripennis , which led to the disruption of sexual communication and foraging behavior (Cook et al, 2016; Tappert et al, 2017). Furthermore, in Solenopsis invicta , when treated with 0.25 μg/ml IMD, there was a significant reduction in food consumption, digging and foraging behavior, while the neurotoxins flubendiamide and indoxacarb increased the walking time of Copidosoma truncatellum (Wang L. et al, 2015; Ramos et al, 2018). In the current work, we found that nAChRa4 and nAChRb1 were down-regulated, which was consistent with the expression of nAChRs in Rhopalosiphum padi (Wang K. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…IMD was thought to impede information receiving and processing in N. vitripennis , which led to the disruption of sexual communication and foraging behavior (Cook et al, 2016; Tappert et al, 2017). Furthermore, in Solenopsis invicta , when treated with 0.25 μg/ml IMD, there was a significant reduction in food consumption, digging and foraging behavior, while the neurotoxins flubendiamide and indoxacarb increased the walking time of Copidosoma truncatellum (Wang L. et al, 2015; Ramos et al, 2018). In the current work, we found that nAChRa4 and nAChRb1 were down-regulated, which was consistent with the expression of nAChRs in Rhopalosiphum padi (Wang K. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides that belong to the chemical group of organophosphates and carbamates, such as methomyl, are known to cause high and rapid mortality (Turchen et al 2015, Ramos et al 2018, and are generally considered to be broad spectrum compounds that have a low selectivity to natural enemies (Fukuto 1990, Hemingway et al 1993.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity exerted by these two chemical groups is related to their low molecular masses (Bacci et al 2007), which allow an easy penetration into the insect cuticle (Stock & Holloway 1993) and a high mortality rate, as observed affecting the behavior of parasitic wasps of Copidosoma truncatellum (Dalman) (Hymenoptera: Encyrtidae), when exposed to nine insecticides containing methomyl, which caused 100 % of mortality (Ramos et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the spinozines obtained from secondary metabolism of Saccharopolyspora spinose, act as allosteric modulator of nicotinic receptor of the post-synaptic nerve in insects (Salgado and Saar, 2004). Further, diamides, the newest mode of action to be introduced for pest control, act as modulator of ryanodine channels with high selectivity for natural enemies (Ramos et al, 2018;Pazini et al, 2016). (Roditakis et al, 2017;Troczka et al, 2012).…”
Section: Resultsmentioning
confidence: 99%